Neuro-Metabolite Changes in a Single Season of University Ice Hockey Using Magnetic Resonance Spectroscopy - Panchal, Hemali; Sollmann, Nico; Pasternak, Ofer; Alosco, Michael L.; Kinzel, Philipp; Kaufmann, David; Hartl, Elisabeth; Forwell, Lorie A.; Johnson, Andrew M.; Skopelja, Elaine N.; Shenton, Martha E.; Koerte, Inga K.; et al. (Frontiers in Neurology, 2018)
Background: Previous research has shown evidence for transient neuronal loss after repetitive head impacts as demonstrated by a decrease in N-acetytaspartate (NAA). However, few studies have investigated other neuro-metabolites that may be altered in the presence of repetitive subconcussive head impacts (RSHI). Objective: The aim of this study was to identify alterations in brain metabolites over time as well as to characterize sex-specific differences in response to RSHI. Methods: Thirty-three collegiate ice hockey players (17 males and 16 females) underwent 3T magnetic resonance spectroscopy (MRS) of the corpus callosum and neurocognitive evaluation before and after the Canadian Interuniversity Sports (CIS) ice hockey season 2011-2012. The MRS voxel was placed in the corpus callosum. Pre- and postseason neurocognitive performances were assessed using the Immediate Post-Concussion Assessment and Cognitive Test (ImPACT). Results: A significant decrease in NAA was observed from preseason to postseason (p=0.001). Furthermore, a trend towards a decrease in total choline (Cho) was observed (p=0.044). Although no overall effect was observed for glutamate (Glu) over the season, a difference was observed with the females showing a decrease in Glu and males showing an increase in Glu, though this was not statistically significant (p=0.039). In both males and females, a negative correlation was observed between changes in Glu and changes in verbal memory (p=0.008). Conclusion: The results of this study demonstrate changes in absolute concentrations of neuro-metabolites following exposure to RSHI. Results suggest that changes in Glutamate are correlated with changes in verbal memory. Future studies need to investigate further the association between brain metabolites and clinical outcome as well as sex-specific differences in the brain’s response to RSHI.